2010
DOI: 10.1094/cchem-06-10-0087
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Alkaline Cooking Performance of Selected Corn and Sorghum Hybrids

Abstract: Cereal Chern. 87(6):524-531Dent com (Zea mays L.) and sorghum (Sorghum hieolor L. Moench) sample sets representative of commonly grown hybrids and diverse physical attributes were analyzed for alkaline cooking performance. The influence of kernel characteristics including hardness, density, starch properties (thermal. pasting, and crystallinity). starch content. protein content. and prolamin content on alkaline cooking performance was also determined. Com nix tarnal moisture content was lower for hard, dense k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
7
14
0
Order By: Relevance
“…Protein content were 8.72, 10.54% in raw green and white faba bean, respectively. These results are in agreement with Johnson et al (2010) who found that crude protein content in whole faba bean grain is ranged from 7 to 15% or 10.30 to 14.90%.…”
Section: Resultssupporting
confidence: 93%
“…Protein content were 8.72, 10.54% in raw green and white faba bean, respectively. These results are in agreement with Johnson et al (2010) who found that crude protein content in whole faba bean grain is ranged from 7 to 15% or 10.30 to 14.90%.…”
Section: Resultssupporting
confidence: 93%
“…In a companion study, the environment was found to have the largest effect on variation in grain yield, kernel mass, kernel density, and kernel composition; the hybrid to have an intermediate effect; and the environment‐by‐hybrid interaction to have minor importance, accounting for less than 2% of the total variation (Griess et al, 2010). This research indicated that dryland production environments with a nonlimiting N supply produced dense sorghum kernels with high protein and low starch concentrations, as also reported by Johnson et al (2010), Taylor et al (1997), and Kaye et al (2007), whereas irrigated production environments produced softer grain. Asgrow Orbit and ICRISAT Macia produced the densest kernels with high protein and low starch concentrations, whereas Kelly Green Seeds KG6902; NC+ Hybrids 7W92; and Fontanelle W‐1000 produced soft kernels with low protein and high starch concentrations (Griess et al, 2010).…”
supporting
confidence: 83%
“…These results indicated that starch granules in the flour from this environment hydrated more slowly (due to the thick protein matrix surrounding the starch granules) and took longer to gelatinize, that the flour slurry was less stable during shear‐force thinning, and that the aligned starch molecules did not reassociate well with each other. Grain produced in this environment would therefore be well suited for food products made by dry milling (Johnson, 2005) and alkaline cooking (Almeida‐Dominguez et al, 1997; Johnson et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Quality factors of maize had a narrow range for TW but wider for KS, TKW, TADD, and also for NIT Milling Index (Table IV) (2007) and Johnson et al (2010). TADD hardness was remarkably similar for maize (33.8% ± 6.6%) and sorghum (35.1% ± 7.0%).…”
Section: Resultsmentioning
confidence: 98%